Practice makes imperfect: a discussion of revenue practice note 24 and related issues - Abdullah, Nathiera (Department of Public Law, 2024)
Revenue Practice Note 24 dated 8 August 1994 reads as follows: "Self-employed taxpayers must claim their motor vehicle expenses based on the actual cost incurred in respect of such vehicle over the· actual distance travelled. The private use of the vehicle must, therefore, lie based on actual figures. To reduce the workload for both taxpayers and Inland Revenue, it is acceptable in cases where a taxpayer has not maintained adequate records, to base the private use of the vehicle on the value determined in terms of paragraph 7(4) of the Seventh Schedule to the Income Tax Act." Paragraph 7(4) of the Seventh Schedule to the Income Tax Act, 58 of 1962, as amended, ("the Act") provides that employees are to be taxed on a value of 1,8 per cent per month of the "determined value" of a motor vehicle, the use of which is granted to them by virtue of their employment. The determined value of a vehicle is its cost excluding finance charges and VAT, and the amount obtained by multiplying this cash cost exclusive of VAT by 1,8 per cent per month is reduced by R120 per month where the employee bears the cost of all fuel used for the purposes of the private use of the vehicle, and by a further R85 per month where the employee bears the full cost of maintaining the vehicle (including the cost of repairs, servicing, lubrication and tyres).